Combinations of fixation methods for adolescent forearm diaphysis fractures - Gulcek, Murat (Annals of Medical Research, 2021)
Aim: There is no consensus on treatment of forearm both bone diaphysis fractures in adolescents. In this study, we report the results of intramedullary fixation, plate-screw fixation, and combination of those methods in forearm fractures of adolescents. Materials and Methods: A total of 62 patients that were surgically treated, and completed their treatments in 11-year period (2003-2014) were included in the study. The forearm diaphysis double bone fracture was fixated with intramedullary nail in 23 adolescents. Both bones were fixated with plate-screw in 20 adolescents. In 19 patients, one bone was fixated with intramedullary nail, the other was fixated with plate-screw. Clinical results were graded in accordance with Price classification system. Results: Three treatment groups were similar for clinical success. All three methods may be used with success rates of 65-75%.Conclusions: The surgeon may choose intramedullary nail, plate-screw or their combination in accordance with the results of closed reduction maneuver in treatment of adolescent forearm double diaphysis fractures.
Keywords: Bone plate; bone wire; pediatric; radius fracture; ulna fracture